Antena Kupu - Kupu Sebagai Sensor Ultra High Frequency (UHF) Untuk Mendeteksi Partial Discharge Pada Gas Insulation Substation - Andre, Hanalde; Khayam, Umar (Jurusan Teknik Elektro Universitas Andalas, 2013)
The use of antennas as receiving electromagnetic waves can be used as a tool for the detection of partial discharge (PD) that occurs in high voltage equipment. Especially in the insulation gas substation (GIS), the characteristics of the electromagnetic waves generated lies in the range of ultra high frequency (UHF) in the range of 300 MHz - 3 GHz. Characteristics of the antenna ultra wide band (UWB) is required to detect PD in a wide range. Antenna design is done using a simulation with finite element method or finite element method (FEM). Characteristics of return loss (RL) to be considered in the design of the antenna to get better sensitivity yan. Antenna testing is done with vector network analyzer (VNA). Measurement and simulation results of the modified antennas showed a decrease in the value of RL.Keywords : Partial Discharge (PD), Antena, Ulltra High Frequency (UHF),Gas Insulation Substation (GIS) AbstrakPenggunaan antena sebagai penerima gelombang elektromagnetik dapat digunakan sebagai alat untuk mendeteksi kegiatan partial discharge (PD) yang terjadi pada paralatan tegangan tinggi. Khususnya pada gas insulation substation (GIS), karakteristik gelombang elektromagnetik yang dihasilkan terletak pada rentang ultra high frequency (UHF) dalam rentang 300 MHz – 3 GHz. Karakteristik antena ultra wide band (UWB) diperlukan untuk mendeteksi PD pada rentang yang lebar. Perancangan antena dilakukan menggunakan simulasi dengan metoda elemen hingga atau finite element method (FEM). Karakteristik return loss (RL) antena dipertimbangkan dalam perancangan untuk mendapatkan sensitivitas yan lebih baik. Pengujian antena dilakukan dengan vector network analyzer (VNA). Hasil pengukuran dan simulasi antena yang dimodifikasi menunjukkan penurunan nilai RL. Keywords : Partial Discharge (PD), Antena, Ulltra High Frequency (UHF),Gas Insulation Substation (GIS)